Effectiveness of Performance Based Contracts in Managing Road Maintenance - Syarifuddin, Mochamad Faisal Syarifuddin Faisal; -, Sutarsono, -; -, Sriyono -; -, Berghans - (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2020)
Budget limitations require the need for a special strategy in maintaining national roads. The main problem with Indonesia’s road maintenance is the fact that the functional and structural conditions of the roads are damaged before their design life. The damage is caused by several factors, including (1) inadequate planning and design, (2) errors during construction, (3) lack of supervision of vehicle loads during road operations and (4) inaccurate road maintenance strategies. This study uses the Qualitative Analysis method. This study outlines the benefits of implementing a Performance Based Contract (PBC) in handling road maintenance. The data used are primary data obtained from interviews and direct observations. The secondary data obtained by literacy studies from the literature, planning documents and budgeting. Data analysis was performed by comparing the implementation of a performance-based contract system (PBC) with a conventional system. The results of the study concluded that the PBC pilot project in handling road maintenance was far more efficient and effective. If PBC is to be implemented broadly, it is recommended to prepare regulations that can reduce obstacles in its implementation.